Sharia Compliance in the Management of Selvira Guesthouse - Peter Febrian; Najamuddin Najamuddin; Ahmad Fuad (Journal Of Social Siences And Islamic Studies (JOSIS), 2025)
This study was conducted to address the following issues: (1) how is the operational management of Wisma Selvira implemented; (2) how is the operational management of Wisma Selvira based on the DSN-MUI Fatwa No. 108/DSN-MUI/X/2016 implemented. The objectives of this study are (1) to find out how the operational management of Wisma Selvira is carried out, and (2) to understand how Wisma Selvira’s operations align with the DSN-MUI Fatwa No. 108/DSN-MUI/X/2016. This research uses a descriptive qualitative approach with data collection techniques through direct observation, interviews, and documentation. The data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study show that (1) although Wisma Selvira does not officially have the status of a Sharia hotel, its operational implementation is already aligned with values consistent with Sharia principles, as seen from various aspects such as guest admission procedures, facility provision, and human resource management. (2) Wisma Selvira lodging has demonstrated concrete efforts to apply management principles oriented toward Sharia values, although it has not fully met the formal requirements as a Sharia hotel according to DSN-MUI Fatwa No. 108/DSN-MUI/X/2016.